Insight on Cardiac Chronobiology and Latest Developments of Chronotherapeutic Antihypertensive Interventions for Better Clinical Outcomes - Joshi, Kumud; Das, Madhubanti; Sarma, Anupam; Arora, Mandeep K.; SInghal, Manmohan; Kumar, Bhavna (Current Hypertension Reviews, 2023)
Cardiac circadian rhythms are an important regulator of body functions, including cardiac activities and blood pressure. Disturbance of circadian rhythm is known to trigger and aggravate various cardiovascular diseases. Thus, modulating the circadian rhythm can be used as a therapeutic approach to cardiovascular diseases. Through this work, we intend to discuss the current understanding of cardiac circadian rhythms, in terms of quantifiable parameters like BP and HR. We also elaborate on the molecular regulators and the molecular cascades along with their specific genetic aspects involved in modulating circadian rhythms, with specific reference to cardiovascular health and cardiovascular diseases. Along with this, we also presented the latest pharmacogenomic and metabolomics markers involved in chronobiological control of the cardiovascular system along with their possible utility in cardiovascular disease diagnosis and therapeutics. Finally, we reviewed the current expert opinions on chronotherapeutic approaches for utilizing the conventional as well as the new pharmacological molecules for antihypertensive chronotherapy.
Keywords: cardiovascular risks